Tomato leaves as a sustainable biosorbent for the effective removal of some organic dyes and lead from water - Helmi, Layan; Sunoqrot, Suhair; Hijazi, Akram; Alayli, Maria; Rajha, Hiba N.; Al Bakri, Maram; El-Dakdouki, Mohammad H.; El Darra, Nada (Frontiers in Environmental Science, 2025)
IntroductionWater, an essential component for life and agriculture, is increasingly threatened by contamination. Industrial wastewater is a major source of pollution that continues to negatively impact ecosystems and human health. It contains contaminants such as dyes, heavy metals, pharmaceuticals, and pesticides, emphasizing the urgent need for effective water purification methods. This study investigates the valorization of tomato leaves as a potential adsorbent for these pollutants.MethodsCharacterization of untreated and contaminant-treated tomato leaves by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microcopy (SEM), confirmed the presence of significant functional group interactions and surface active sites suited for adsorption.ResultsTomato leaves demonstrated significant adsorption capabilities for contaminants like methylene blue, malachite green, crystal violet, and lead, achieving removal efficiencies of 90.7% ± 0.3, 93.6% ± 0.5, 89.8% ± 0.6, and 78.4% ± 0.2, respectively, at an initial contaminant concentration of 20 mg/L. High adsorption effectiveness was also observed across various dye concentrations (5-25 mg/L) and contact times (5-120 min). Isotherm analysis indicated that lead adsorption followed the Langmuir model and Henry adsorption isotherm with a maximum adsorption capacity of 45.77 mg/g, while dyes aligned with the Freundlich model, with adsorption kinetics best fitting the pseudo-second order model in all cases.DiscussionTo our knowledge, this is the first study to comprehensively evaluate the adsorption of both heavy metals (Pb2+) and three structurally different cationic dyes using raw, unmodified tomato leaves. This provides a sustainable, cost-effective, and green solution for the removal of diverse pollutants from water. Future work can explore enhancing the efficiency of decontamination and real-life application, including performing field trials in diverse environmental and industrial wastewater scenarios.